2015
DOI: 10.1007/s10509-015-2391-7
|View full text |Cite
|
Sign up to set email alerts
|

Ion-acoustic solitons in plasma: an application to Saturn’s magnetosphere

Abstract: Soliton formation in plasma is addressed. Nonlinear acoustic waves in plasma where the combined effects of bounded spherical geometry and the transverse perturbation are dealt with, in two-temperature electron plasma are studied. Using the perturbation method, a spherical KadomtsevPetviashvili equation (SKP) that describes the ion acoustic waves is derived. The plasma is modeled by a kappa distribution function for both electrons components as found in Saturn's magnetosphere. It is found that parameters taken … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…[21][22][23][24][25] Based on the plasma kinetic theory, the modified Boltzmann relation for the Kappa distributed particles are derived and the effect of superthermality of the electrons on the characteristics of the ion-acoustic solitons are investigated. 26) Using this modified Boltzmann relations, the arbitrary amplitude ion-acoustic solitary waves in the Lorentzian plasmas, 27) the electron-acoustic solitary structures in two-electron-temperature plasma, 28) the ion-acoustic solitons in Saturn's magnetosphere 29) were investigated.…”
Section: Introductionmentioning
confidence: 99%
“…[21][22][23][24][25] Based on the plasma kinetic theory, the modified Boltzmann relation for the Kappa distributed particles are derived and the effect of superthermality of the electrons on the characteristics of the ion-acoustic solitons are investigated. 26) Using this modified Boltzmann relations, the arbitrary amplitude ion-acoustic solitary waves in the Lorentzian plasmas, 27) the electron-acoustic solitary structures in two-electron-temperature plasma, 28) the ion-acoustic solitons in Saturn's magnetosphere 29) were investigated.…”
Section: Introductionmentioning
confidence: 99%
“…It is observed that in the presence of hot and cold electrons, the potential profiles get modified significantly and result in the formation of compressive and rarefactive distributions (see Figures 1a, 2 and 7) and are in good agreement with the earlier theoretical studies by Siani et al [ 19 ] and K. Annou. [ 54 ] The rotational frequency is also found to affect the potential profiles significantly as can be seen in Figures 6 and 9. Further, we have used generalized Lorentzian distribution for electrons by taking values of kappa in the range 2–6 that are representative of space plasma environments.…”
Section: Discussionmentioning
confidence: 85%
“…The first experimental measurements of standing IA waves were reported by Revans [2] in 1933, whereas the observation of propagating IA waves took another 33 years, and it was reported by Wong et al [3] in the Q machine in 1962. The IA wave has also been observed in astrophysical plasmas, such as solar wind [4], Saturn ring [5], Comets, Neutrinos [6], Magnetosphere as well as in fusion plasmas.…”
Section: Imentioning
confidence: 95%